Can Supervised Pelvic Floor Muscle Training Through Gametherapy Relieve Urinary Incontinence Symptoms in Climacteric Women? A Feasibility Study - Anita Bellotto Leme Nagib; Valeria Regina Silva; Natalia Miguel Martinho; Andrea Marques; Cassio Riccetto; Simone Botelho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To investigate the feasibility of pelvic floor muscle training (PFMT) through gametherapy for relieving urinary symptoms of climacteric women with stress ormixed urinary incontinence (UI). Methods Randomized clinical trial, divided into two groups: Gametherapy (G_Game) and Control (G_Control). Both groups received recommendations about unsupervised PFMT, and G_Game also received supervised PFMT through gametherapy. After 5 consecutive weeks, the feasibility was investigated considering participant adherence, urinary symptoms (evaluated by the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form [ICIQ-UI-SF] questionnaire), and pelvic floor function (PERFECT Scheme: power, endurance, repetition and fast). The Fisher exact, Kruskal-Wallis, Wilcoxon sign paired, and Mann-Whitney U tests were used by intention-to-treat analysis, using STATA 15.1 (StataCorp, College Station, TX, USA) software. Results The present study included 20 women per group and observed a higher adherence in G_Game. In the intragroup analysis, a decrease in the ICIQ-UI-SF score was observed in both groups (14.0 to 10.0; 13.5 to 0), associated with increased endurance (2.5 to 3.5; 2.5 to 4.0) in G_Control and G_Game, respectively. Moreover, there was a concomitant increase in pelvic floor muscles (PFMs) power (2.0 to 3.0), repetition (3.0 to 5.0), and fast (10.0 to 10.0) in G_Game. In the intergroup analysis, a reduction of UI was observed (p<0.001; r=0.8), as well an increase in PFM power (p=0.027, r=0.2) and endurance (p=0.033; r=0.3) in G_Game. Conclusion The feasibility of supervised PFMT through gametherapy was identified by observing participant adherence, relief of urinary symptoms, and improvement in PFM function.